Gut microbiota and changes in cytokine profile in animals with experimental acute disseminated peritonitis on the background of diabetes - B. M. Verveha; B. V. Gutyj; M. I. Holubiev; M. M. Kondro; І. V. Dats (Regulatory Mechanisms in Biosystems, 2023)
In the pathogenesis of acute widespread peritonitis and accompanying diabetes, a vital link is an endogenous intoxication caused by the translocation of microorganisms and their toxins from the intestine into the blood, metabolic changes, and immunological reactivity of the body. Our work aimed to investigate the microbial composition in the parietal intestinal biotope and the features of the blood cytokine profile in animals with acute disseminated peritonitis on the background of streptozotocin-induced diabetes. The study was conducted on 56 sexually mature non-linear white male rats. Diabetes mellitus was modeled by a single intraperitoneal injection of streptozotocin (60 mg/kg). On the 14th day of the development of streptozotocin-induced diabetes mellitus, a 10% filtered fecal suspension (0.5 mL) was injected into the abdominal cavity of animals, and acute generalized peritonitis was initiated. Sowing on nutrient media was carried out for bacteriological research to isolate a pure culture of microorganisms and their identification. The concentration of TNF-α, IL-1β, and IL-6 was studied by solid-phase enzyme immunoassay. The research results demonstrate an imbalance of cytokines in the dynamics of experimental acute disseminated peritonitis against the background of diabetes and quantitative and qualitative changes in the microbiota of the parietal intestinal biotope. A decrease in the number of Escherichia coli strains isolated in monoculture and an increase in the number of two-component and three-component microbial associations were revealed, among which Enterobacter aerogenes, Escherichia coli, Bacteroides spp., Proteus mirabilis, Klebsiella spp. and Candida species prevailed.